Sodium chloride accumulation in glycophyte plants with cyanobacterial symbionts - Green, Thomas George Allan (AoB Plants, 2017)
The majority of plant species are glycophytes and are not salt-tolerant and maintain low sodium levels within their tissues; if(.) high tissue sodium concentrations do occur, it is in response to elevated environmental salt levels. Here we report an apparently novel and taxonomically diverse grouping of plants that continuously maintain high tissue sodium contents and share the rare feature of possessing symbiotic cyanobacteria. Leaves of Gunnera magellanica in Tierra del Fuego always had sodium contents (dry weight basis) of around 4.26 g kg(−1), about 20 times greater than measured in other higher plants in the community (0.29 g kg(−1)). Potassium and chloride levels were also elevated. This was not a response to soil sodium and chloride levels as these were low at all sites. High sodium contents were also confirmed in G. magellanica from several other sites in Tierra del Fuego, in plants taken to, and cultivated in Madrid for 2 years at low soil salt conditions, and also in other free living or cultivated species of Gunnera from the UK and New Zealand. Gunnera species are the only angiosperms that possess cyanobacterial symbionts so we analysed other plants that have this rather rare symbiosis, all being glycophytes. Samples of Azolla, a floating aquatic fern, from Europe and New Zealand all had even higher sodium levels than Gunnera. Roots of the gymnosperm Cycas revoluta had lower sodium contents (2.52 ± 0.34 g kg(−1)) but still higher than the non-symbiotic glycophytes. The overaccumulation of salt even when it is at low levels in the environment appears to be linked to the possession of a cyanobacterial symbiosis although the actual functional basis is unclear.